Development of e-module integrated QR code in a lesson of Air Conditioner (AC) to support paperless - Rahmatia Joisangadji; Subagyo Subagyo; Bayu Rahmat Setiadi (Jurnal Taman Vokasi, 2018)
This was Research and Development. This research aimed to develop an integrated QR-code e-module to support the paperless movement in the air conditioner (AC) course, and to find out the feasibility of media e-modules and the response of students of Mechanical Engineering Education. The results of this study were: 1) the integrated QR-code e-module product to support the paperless movement in the air conditioner (AC) course, 2) the air conditioner e-module was declared feasible by experts with a percentage of feasibility by material experts of 100%, from the results e-modules worthy of product testing. In the product trial, the results of the readability of e-module media in 20 students obtained an overall score of 1767 indicating "very feasible" with a percentage of 88.35%. In testing the use of the results of the readability of e-module media; 50 students obtained an overall score of 4128 indicating "feasible" with a percentage of 82.56%, so it could be said that the e-module developed was feasible to be used as a learning media for the manufacture of AC and accessories.